Some “Heterodox” Explanations of the Economic Crisis - Nicholas Sowels (Revue Française de Civilisation Britannique)
This article starts by noting that the financial crisis of 2007-2008 was not an accident, but the result of financial liberalisation in the preceding decades which had led to periodic and increasingly violent financial crises from the 1980s onwards. The article moves on to review the increasing difficulty that policies implemented to overcome the crisis and the Great Recession have in stimulating growth today, focussing on the UK. The article proceeds by noting that neoliberalism has led to rising inequalities. As a result, the relationship between capital and labour is not only more confrontational but households are also suffering stagnant income growth, and so are constrained in contributing to aggregate demand. In some ways, it therefore appears that pressure on profits and wages is making capitalism more unstable and inherently subject to crises, as analysed by Marx during the age of 19th century liberalism. At the same time, the greater financialisation of national and the global economies means that they are more subject to economic shocks arising from financial crises, when the “fictitious” nature of financial assets is revealed, also discussed by Marx in Capital.